Distinct Genomic Landscape of Colorectal Mucinous Carcinoma Determined via Comprehensive Genomic Profiling: Steps to a New Treatment Strategy - Huang, Liang; Luo, Shuanglin; Zhang, Xingwei; Cai, Yonghua; Xue, Fangqin; Hu, Huanxin; Zeng, Ziwei; Lin, Tengjiao; Wang, Fei; Wang, Weifeng; Zhang, Sen; Kang, Liang (Frontiers in Oncology, 2021)
Colorectal mucinous carcinoma (MC) is associated with inferior prognosis and response to treatment compared to adenocarcinoma (AC). The molecular landscapes of MC and adenocarcinoma with mucous composition (AMC) are not well-defined. We aimed to describe the genomic landscape of MC and AMC in a large colorectal cancer cohort. Tumor samples from patients with MC, AMC, or AC were analyzed using next-generation sequencing. MC had a molecular signature distinct from that of AC; genomic features were similar between AMC and MC but not between AMC and AC. HER2 amplification and TP53 and APC mutation rates were lower, whereas SMAD4, PIK3CA, ACVR2A, KMT2D, LRP1, TGFBR2, GRIN2A, BRAF V600E, PTEN, and BRCA2 mutation rates were higher in MC than in AC. The mutation frequencies in MAPK, PI3K, and TGF-β pathways were higher, whereas those of cell cycle proteins and Wnt were lower in MC and AMC than in AC. The proportion of hypermutated tumors was significantly higher in MC and AMC than in AC. As MC has a distinct molecular signature from AC, immunotherapy can be potentially applied in treating MC. Similar molecular profiles of AMC and MC suggest that treatment strategies for MC, but not AC, can be used for AMC treatment.